2004
DOI: 10.1002/ijc.20210
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of familial pancreatic cancer in Germany

Abstract: Based on several case-control studies, it has been estimated that familial aggregation and genetic susceptibility play a role in up to 10% of patients with pancreatic cancer, although conclusive epidemiologic data are still lacking. Therefore, we evaluated the prevalence of familial pancreatic cancer and differences to its sporadic form in a prospective multicenter trial. A total of 479 consecutive patients with newly diagnosed, histologically confirmed adenocarcinoma of the pancreas were prospectively evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 42 publications
5
48
1
4
Order By: Relevance
“…2,17 It has been suggested recently that the RNA-SEL variants Glu265X and Arg462Gln are associated with an increased risk for sporadic 13 and familial prostate cancer. 11,12,[18][19][20] Carpten et al 11 first reported a Glu265X mutation that segregated with the disease in one of the HPC1-linked prostate cancer families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,17 It has been suggested recently that the RNA-SEL variants Glu265X and Arg462Gln are associated with an increased risk for sporadic 13 and familial prostate cancer. 11,12,[18][19][20] Carpten et al 11 first reported a Glu265X mutation that segregated with the disease in one of the HPC1-linked prostate cancer families.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological data suggest that dominant susceptibility genes may be responsible for about 3% of all pancreatic cancer cases. 2,3 BRCA2 germline mutations have been identified in 4.9% and 7.3% of apparently sporadic PC cases 4,5 and about 17% of and familial pancreatic cancer (FPC) cases, 6,7 respectively. There is also some evidence that mutations in CDKN2a, PRSS1, Mismatch-Repair and Fanconi anaemia genes predispose to PC, but the contribution of these genes to PC tumorigenesis is considered to be small.…”
mentioning
confidence: 99%
“…An estimated 2.7% to 10% of pancreatic cancers occur in families where there is at least one other case (5)(6)(7)(8). In some instances, this is associated with a general familial cancer syndrome, such as familial atypical multiple-mole melanoma syndrome, familial adenomatous polyposis, hereditary nonpolyposis colorectal cancer, hereditary breast-ovarian cancer syndrome, and Peutz-Jeghers syndrome (9)(10)(11)(12)(13), although in most cases, these syndromes are associated with isolated rather than multiple cases of pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…About 3% to 16% of pancreatic cancer is thought to be either syndromic or familial (15)(16)(17)(18)(19)(20)(21)(22), due to multiorgan cancer syndromes, other genetically driven chronic diseases, or familial groupings of pancreatic cancer with yet unidentified genetic abnormalities (familial pancreatic cancer; ref. 23).…”
mentioning
confidence: 99%